(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
Fifteen single crosses were produced using half diallel fashion in 2016 and they were evaluated in 2017 season at the Agriculture Scientific Research Station at Al-Jmash, Tartous, Syria. To study combining ability for silking date , plant and ear height and grain yield per plant . In order to determine the genetic function that controls the inheritance of traits determining the grain yield . Thus increasing the effectiveness of the process of election and access to Individual Crosses species , The results can be summarized as follows: The variance of both crosses and general combining ability were highly significant for all traits , while it was significant for silking and grain yield Per plant indicating that inbred lines had variation and genetic diversity, and effective of Both additive and non-additive genetic in the inheritance of all studied traits. The ratio between σ2GCA/σ2SCA showed that Non- additive genetic effects were involved of inheritance of grain yield per plant , while additive genetic variance effects were involved of inheritance of days to silking, plant and ear height .The parental inbred lines L1 (IL.262) seemed to be the best combiner for days to silking , parental inbred line (IL.257) was the best combiner for Plant height , parental inbred line L6 (IL.1189) for ear height And parental inbred line (IL.341) for grain yield Per plant . The highest desirable SCA effects were recorded in the hybrid (IL. 257 × IL.1512-09) for days to silking , while hybrid (IL.262 × IL.1189) for grain yield per plant Followed by both hybrids (IL.341 × IL.1512-09) , (IL.341 × IL.257) . تم تكوين خمسة عشر هجيناً فردياً وفق طريقة التهجين نصف المتبادل بين ستة سلالات مرباة داخلياً من الذرة الصفراء خلال موسم 2016 وتم تقييم الهجن الفردية في موسم 2017 ، ضمن محطة بحوث الجماسة ، التابعة لمركز البحوث العلمية الزراعية في محافظة طرطوس، لدراسة المقدرة على الائتلاف لصفات عدد الأيام من الزراعة حتى ظهور 50% من النورات المؤنثة ، ارتفاع النبات ، ارتفاع العرنوس و إنتاجية النبات الفردي ، وذلك لتحديد الفعل المورثي المسيطر على وراثة الصفات الأكثر ارتباطا بالغلة الحبية ، مما يؤدي إلى زيادة فعالية عملية الانتخاب والوصول إلى الهجن الفردية المتميزة، ويمكن تلخيص النتائج بما يلي: كان التباين العائد للهجن وللمقدرة العامة (GCA) على الائتلاف، عالي المعنوية في كل الصفات المدروسة بينما كان تباين المقدرة الخاصة (SCA) معنويا لصفتي الازهار وانتاجية النبات الفردي وهذا يدل على التباعد الوراثي والاختلافات الوراثية بين السلالات المستخدمة في الدراسة وكذلك مساهمة كل من الفعل الوراثي التراكمي واللاتراكمي في وراثة الصفات المدروسة. أظهرت النسبة مابين تباين المقدرة العامة والخاصة على الائتلاف (σ2GCA/σ2SCA) أهمية الفعل الموراثي اللاتراكمي في وراثة صفة انتاجية النبات الفردي ، في حين سيطر الفعل الموراثي التراكمي على كل من صفة الازهار المؤنث ، ارتفاع النبات وارتفاع العرنوس . تميزت السلالة (IL.262) بأفضل مقدرة عامة على الائتلاف لصفة الازهار المؤنث ، السلالة (IL.257) لصفة ارتفاع النبات ، السلالة L6 (IL.1189) لصفة لصفة ارتفاع العرنوس والسلالة (IL.341) لصفة انتاجية النبات الفردي، وأبدى الهجين (IL.257×IL.1512-09) أفضل مقدرة خاصة على الائتلاف لصفة الازهار المؤنث في حين حقق الهجين (IL.262×IL.1189) أفضل مقدرة خاصة على الائتلاف لصفة انتاجية النبات الفردي تلاه كل من الهجينين (IL.341×IL.257) ، (IL.341×IL.1512-09) .